Helping Scientists, Engineers to Work Up to 100 Times Faster. - Guo, Philip; Murphy, Nicholas; Guzdial, Mark; Monagan, Michael (Communications of the ACM, 2013)
In this article the author explains how computer programming skills can boost the efficiency and creativity of scientists and engineers. He presents the story of his friend who works in oceanography and mechanical engineering but spends 95% of his time in front of the computer writing programs to collate and analyze data collected in the field. He also cites several reasons to learn computer programming including discovering more creative solutions, working 10 times faster, and communicating effectively with programmers.